2021
DOI: 10.3390/molecules26092446
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants in Potatoes: A Functional View on One of the Major Food Crops Worldwide

Abstract: With a growing world population, accelerating climate changes, and limited arable land, it is critical to focus on plant-based resources for sustainable food production. In addition, plants are a cornucopia for secondary metabolites, of which many have robust antioxidative capacities and are beneficial for human health. Potato is one of the major food crops worldwide, and is recognized by the United Nations as an excellent food source for an increasing world population. Potato tubers are rich in a plethora of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 318 publications
(348 reference statements)
0
25
0
Order By: Relevance
“…Vitamin C is well-known by consumers for its contribution to immune defense, but it is also a strong antioxidant and a co-factor of several regulatory enzymes [6]. Other phytonutrients, such as carotenoids, flavonoids and phenolic acids, increase the beneficial properties of potato-derived products thanks to their well-characterized antioxidant and human health-promoting properties [7]. Polyphenols are considered potent inhibitors of inflammations, obesity and cardiovascular disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin C is well-known by consumers for its contribution to immune defense, but it is also a strong antioxidant and a co-factor of several regulatory enzymes [6]. Other phytonutrients, such as carotenoids, flavonoids and phenolic acids, increase the beneficial properties of potato-derived products thanks to their well-characterized antioxidant and human health-promoting properties [7]. Polyphenols are considered potent inhibitors of inflammations, obesity and cardiovascular disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant activity was lower in the red-skinned potatoes due to the lower content in anthocyanins compared to purple-fleshed varieties [ 28 ]. The health effects of antioxidant compounds, mediated by their radical scavenging activity, are well-known [ 29 ] and other studies reported that the pigmented potato varieties had the highest antioxidant capacity [ 9 , 28 , 30 ]. Thus suggesting that these cultivars for selection for a healthy human diet.…”
Section: Resultsmentioning
confidence: 99%
“…The composition and accumulation of anthocyanins were analyzed according to C.E. Lewis et al [15]. To determine the content of anthocyanins, we used pulp tissue and tuber skin.…”
Section: Methodsmentioning
confidence: 99%